On The State of the SympatheticAdrenal System and Cytokine Status in Patients with Ischemic Heart Disease by Familial Hypercholesterolemia (Eurasian Medical Research Periodical, 2022)
The article presents the features of disorders of the sympathetic-adrenal system and cytokine status in patients with ischemic heart disease and familial hypercholesterolemia. The study included 144 men and women aged 18 to 65 years, with an average age of 43.8±7.2 years and 15 practically healthy individuals aged 20 to 50 years, with an average age of 41.4±3.5 years. Clinical, instrumental and special research methods were performed. It was found that familial hypercholesterolemia has marked changes in the sympathoadrenal system and cytokine status, which are more pronounced in patients with AHS with clinical signs of CHD